Kreativitas Guru PAI Dalam Menggunakan Media Pembelajaran Sebagai Upaya Meningkatkan Keaktifan Minat dan Belajar Siswa SMPN 2 Sungai Pua Kabupaten Agam - Suhartono, Dinda; J, Jasmienti (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This research was written from a phenomenon experienced by PAI teachers, namely that PAI teachers still do not use and maximize the learning media provided by the school. In this case, there is still a lack of use of media by teachers in increasing students' interest in learning. The aim of this research is to increase the creativity of PAI teachers when using learning media to increase students' activeness and interest in learning. The method used in this research is descriptive research with a qualitative approach. The data usage techniques used are observation, interviews and documentation. The results obtained from this research are that the media used in class VIII at SMPN 2 Sungai Pua, Agam Regency are visual media such as blackboards and in the form of textbooks that have been provided by the school. Then, in creativity, teachers use learning media in class, namely by using power points (PPT) and audio with learning videos. Furthermore, students' responses regarding PAI teachers' creativity when using media are quite good because it can be seen that during the learning process students are very active in expressing their opinions and ideas and asking questions. Therefore, it can be seen from students' interest in learning, students pay more attention to learning, are enthusiastic, and some are still passive.